AfricaMuseum refuses to release Congo geological archive to US mining company, despite pressure from President Trump - Colin Clapson (VRTNWS, 2026)
The AfricaMuseum in Tervuren (Flemish Brabant) is refusing to hand over geological archive material on Congo to an American mining company that wants to use the data to map valuable raw materials. ‘We want to digitalise the archives ourselves and not leave it to a private company,’ the museum says. Meanwhile, the Trump administration is increasing pressure through diplomatic channels.
United States of America